1 (**************************************************************************)
4 (* ||A|| A project by Andrea Asperti *)
6 (* ||I|| Developers: *)
7 (* ||T|| A.Asperti, C.Sacerdoti Coen, *)
8 (* ||A|| E.Tassi, S.Zacchiroli *)
10 (* \ / This file is distributed under the terms of the *)
11 (* v GNU Lesser General Public License Version 2.1 *)
13 (**************************************************************************)
15 include "nat/compare.ma".
16 include "nat/sigma_and_pi.ma".
18 definition injn: (nat \to nat) \to nat \to Prop \def
19 \lambda f:nat \to nat.\lambda n:nat.\forall i,j:nat.
20 i \le n \to j \le n \to f i = f j \to i = j.
22 theorem injn_Sn_n: \forall f:nat \to nat. \forall n:nat.
23 injn f (S n) \to injn f n.unfold injn.
25 apply le_S.assumption.
26 apply le_S.assumption.
30 theorem injective_to_injn: \forall f:nat \to nat. \forall n:nat.
31 injective nat nat f \to injn f n.
32 unfold injective.unfold injn.intros.apply H.assumption.
35 definition permut : (nat \to nat) \to nat \to Prop
36 \def \lambda f:nat \to nat. \lambda m:nat.
37 (\forall i:nat. i \le m \to f i \le m )\land injn f m.
39 theorem permut_O_to_eq_O: \forall h:nat \to nat.
40 permut h O \to (h O) = O.
41 intros.unfold permut in H.
42 elim H.apply sym_eq.apply le_n_O_to_eq.
46 theorem permut_S_to_permut: \forall f:nat \to nat. \forall m:nat.
47 permut f (S m) \to f (S m) = (S m) \to permut f m.
51 cut (f i < S m \lor f i = S m).
53 apply le_S_S_to_le.assumption.
55 apply (not_le_Sn_n m).
57 rewrite > Hcut1.assumption.
58 apply H3.apply le_n.apply le_S.assumption.
59 rewrite > H5.assumption.
60 apply le_to_or_lt_eq.apply H2.apply le_S.assumption.
61 apply (injn_Sn_n f m H3).
66 definition transpose : nat \to nat \to nat \to nat \def
73 | false \Rightarrow n]].
75 notation < "(❲i↹j❳)n" with precedence 71
76 for @{ 'transposition $i $j $n}.
78 notation < "(❲i \atop j❳)n" with precedence 71
79 for @{ 'transposition $i $j $n}.
81 interpretation "natural transposition" 'transposition i j n =
82 (cic:/matita/nat/permutation/transpose.con i j n).
84 lemma transpose_i_j_i: \forall i,j:nat. transpose i j i = j.
85 intros.unfold transpose.
86 rewrite > (eqb_n_n i).simplify. reflexivity.
89 lemma transpose_i_j_j: \forall i,j:nat. transpose i j j = i.
90 intros.unfold transpose.
91 apply (eqb_elim j i).simplify.intro.assumption.
92 rewrite > (eqb_n_n j).simplify.
96 theorem transpose_i_i: \forall i,n:nat. (transpose i i n) = n.
97 intros.unfold transpose.
99 intro.simplify.apply sym_eq. assumption.
100 intro.simplify.reflexivity.
103 theorem transpose_i_j_j_i: \forall i,j,n:nat.
104 transpose i j n = transpose j i n.
105 intros.unfold transpose.
106 apply (eqb_elim n i).
107 apply (eqb_elim n j).
108 intros. simplify.rewrite < H. rewrite < H1.
110 intros.simplify.reflexivity.
111 apply (eqb_elim n j).
112 intros.simplify.reflexivity.
113 intros.simplify.reflexivity.
116 theorem transpose_transpose: \forall i,j,n:nat.
117 (transpose i j (transpose i j n)) = n.
118 intros.unfold transpose. unfold transpose.
119 apply (eqb_elim n i).simplify.
121 apply (eqb_elim j i).
122 simplify.intros.rewrite > H. rewrite > H1.reflexivity.
123 rewrite > (eqb_n_n j).simplify.intros.
126 apply (eqb_elim n j).simplify.
127 rewrite > (eqb_n_n i).intros.simplify.
128 apply sym_eq. assumption.
130 rewrite > (not_eq_to_eqb_false n i H1).
131 rewrite > (not_eq_to_eqb_false n j H).
132 simplify.reflexivity.
135 theorem injective_transpose : \forall i,j:nat.
136 injective nat nat (transpose i j).
139 rewrite < (transpose_transpose i j x).
140 rewrite < (transpose_transpose i j y).
141 apply eq_f.assumption.
144 variant inj_transpose: \forall i,j,n,m:nat.
145 transpose i j n = transpose i j m \to n = m \def
148 theorem permut_transpose: \forall i,j,n:nat. i \le n \to j \le n \to
149 permut (transpose i j) n.
150 unfold permut.intros.
151 split.unfold transpose.
153 elim (eqb i1 i).simplify.assumption.
154 elim (eqb i1 j).simplify.assumption.
156 apply (injective_to_injn (transpose i j) n).
157 apply injective_transpose.
160 theorem permut_fg: \forall f,g:nat \to nat. \forall n:nat.
161 permut f n \to permut g n \to permut (\lambda m.(f(g m))) n.
162 unfold permut. intros.
164 split.intros.simplify.apply H2.
167 apply H5.assumption.assumption.
168 apply H3.apply H4.assumption.apply H4.assumption.
172 theorem permut_transpose_l:
173 \forall f:nat \to nat. \forall m,i,j:nat.
174 i \le m \to j \le m \to permut f m \to permut (\lambda n.transpose i j (f n)) m.
175 intros.apply (permut_fg (transpose i j) f m ? ?).
176 apply permut_transpose.assumption.assumption.
180 theorem permut_transpose_r:
181 \forall f:nat \to nat. \forall m,i,j:nat.
182 i \le m \to j \le m \to permut f m \to permut (\lambda n.f (transpose i j n)) m.
183 intros.apply (permut_fg f (transpose i j) m ? ?).
184 assumption.apply permut_transpose.assumption.assumption.
187 theorem eq_transpose : \forall i,j,k,n:nat. \lnot j=i \to
188 \lnot i=k \to \lnot j=k \to
189 transpose i j n = transpose i k (transpose k j (transpose i k n)).
190 (* uffa: triplo unfold? *)
191 intros.unfold transpose.unfold transpose.unfold transpose.
192 apply (eqb_elim n i).intro.
193 simplify.rewrite > (eqb_n_n k).
194 simplify.rewrite > (not_eq_to_eqb_false j i H).
195 rewrite > (not_eq_to_eqb_false j k H2).
197 intro.apply (eqb_elim n j).
201 rewrite > (not_eq_to_eqb_false n k Hcut).
203 rewrite > (not_eq_to_eqb_false n k Hcut).
204 rewrite > (eq_to_eqb_true n j H4).
206 rewrite > (not_eq_to_eqb_false k i).
207 rewrite > (eqb_n_n k).
208 simplify.reflexivity.
209 unfold Not.intro.apply H1.apply sym_eq.assumption.
211 unfold Not.intro.apply H2.apply (trans_eq ? ? n).
212 apply sym_eq.assumption.assumption.
213 intro.apply (eqb_elim n k).intro.
215 rewrite > (not_eq_to_eqb_false i k H1).
216 rewrite > (not_eq_to_eqb_false i j).
218 rewrite > (eqb_n_n i).
220 unfold Not.intro.apply H.apply sym_eq.assumption.
222 rewrite > (not_eq_to_eqb_false n k H5).
223 rewrite > (not_eq_to_eqb_false n j H4).
225 rewrite > (not_eq_to_eqb_false n i H3).
226 rewrite > (not_eq_to_eqb_false n k H5).
227 simplify.reflexivity.
230 theorem permut_S_to_permut_transpose: \forall f:nat \to nat.
231 \forall m:nat. permut f (S m) \to permut (\lambda n.transpose (f (S m)) (S m)
233 unfold permut.intros.
235 split.intros.simplify.unfold transpose.
236 apply (eqb_elim (f i) (f (S m))).
237 intro.apply False_ind.
239 apply (not_le_Sn_n m).
240 rewrite < Hcut.assumption.
241 apply H2.apply le_S.assumption.apply le_n.assumption.
243 apply (eqb_elim (f i) (S m)).
245 cut (f (S m) \lt (S m) \lor f (S m) = (S m)).
246 elim Hcut.apply le_S_S_to_le.assumption.
247 apply False_ind.apply H4.rewrite > H6.assumption.
248 apply le_to_or_lt_eq.apply H1.apply le_n.
250 cut (f i \lt (S m) \lor f i = (S m)).
251 elim Hcut.apply le_S_S_to_le.assumption.
252 apply False_ind.apply H5.assumption.
253 apply le_to_or_lt_eq.apply H1.apply le_S.assumption.
255 apply H2.apply le_S.assumption.apply le_S.assumption.
256 apply (inj_transpose (f (S m)) (S m)).
260 (* bounded bijectivity *)
262 definition bijn : (nat \to nat) \to nat \to Prop \def
263 \lambda f:nat \to nat. \lambda n. \forall m:nat. m \le n \to
264 ex nat (\lambda p. p \le n \land f p = m).
266 theorem eq_to_bijn: \forall f,g:nat\to nat. \forall n:nat.
267 (\forall i:nat. i \le n \to (f i) = (g i)) \to
268 bijn f n \to bijn g n.
269 intros 4.unfold bijn.
271 apply (ex_intro ? ? a).
272 rewrite < (H a).assumption.
273 elim H3.assumption.assumption.
276 theorem bijn_Sn_n: \forall f:nat \to nat. \forall n:nat.
277 bijn f (S n) \to f (S n) = (S n) \to bijn f n.
278 unfold bijn.intros.elim (H m).
280 apply (ex_intro ? ? a).split.
281 cut (a < S n \lor a = S n).
282 elim Hcut.apply le_S_S_to_le.assumption.
284 apply (not_le_Sn_n n).
285 rewrite < H1.rewrite < H6.rewrite > H5.assumption.
286 apply le_to_or_lt_eq.assumption.assumption.
287 apply le_S.assumption.
290 theorem bijn_n_Sn: \forall f:nat \to nat. \forall n:nat.
291 bijn f n \to f (S n) = (S n) \to bijn f (S n).
293 cut (m < S n \lor m = S n).
297 apply (ex_intro ? ? a).split.
298 apply le_S.assumption.assumption.
299 apply le_S_S_to_le.assumption.
300 apply (ex_intro ? ? (S n)).
302 rewrite > H3.assumption.
303 apply le_to_or_lt_eq.assumption.
306 theorem bijn_fg: \forall f,g:nat\to nat. \forall n:nat.
307 bijn f n \to bijn g n \to bijn (\lambda p.f(g p)) n.
312 apply (ex_intro ? ? a1).
314 rewrite > H8.assumption.
315 assumption.assumption.
318 theorem bijn_transpose : \forall n,i,j. i \le n \to j \le n \to
319 bijn (transpose i j) n.
320 intros.unfold bijn.unfold transpose.intros.
321 cut (m = i \lor \lnot m = i).
323 apply (ex_intro ? ? j).
325 apply (eqb_elim j i).
326 intro.simplify.rewrite > H3.rewrite > H4.reflexivity.
327 rewrite > (eqb_n_n j).simplify.
328 intros. apply sym_eq.assumption.
329 cut (m = j \lor \lnot m = j).
331 apply (ex_intro ? ? i).
333 rewrite > (eqb_n_n i).simplify.
334 apply sym_eq. assumption.
335 apply (ex_intro ? ? m).
337 rewrite > (not_eq_to_eqb_false m i).
338 rewrite > (not_eq_to_eqb_false m j).
339 simplify. reflexivity.
342 apply (decidable_eq_nat m j).
343 apply (decidable_eq_nat m i).
346 theorem bijn_transpose_r: \forall f:nat\to nat.\forall n,i,j. i \le n \to j \le n \to
347 bijn f n \to bijn (\lambda p.f (transpose i j p)) n.
349 apply (bijn_fg f ?).assumption.
350 apply (bijn_transpose n i j).assumption.assumption.
353 theorem bijn_transpose_l: \forall f:nat\to nat.\forall n,i,j. i \le n \to j \le n \to
354 bijn f n \to bijn (\lambda p.transpose i j (f p)) n.
357 apply (bijn_transpose n i j).assumption.assumption.
361 theorem permut_to_bijn: \forall n:nat.\forall f:nat\to nat.
362 permut f n \to bijn f n.
364 elim n.unfold bijn.intros.
365 apply (ex_intro ? ? m).
367 apply (le_n_O_elim m ? (\lambda p. f p = p)).
368 assumption.unfold permut in H.
369 elim H.apply sym_eq. apply le_n_O_to_eq.apply H2.apply le_n.
370 apply (eq_to_bijn (\lambda p.
371 (transpose (f (S n1)) (S n1)) (transpose (f (S n1)) (S n1) (f p))) f).
372 intros.apply transpose_transpose.
373 apply (bijn_fg (transpose (f (S n1)) (S n1))).
374 apply bijn_transpose.
376 elim H1.apply H2.apply le_n.apply le_n.
379 apply permut_S_to_permut_transpose.
380 assumption.unfold transpose.
381 rewrite > (eqb_n_n (f (S n1))).simplify.reflexivity.
384 let rec invert_permut n f m \def
385 match eqb m (f n) with
390 |(S p) \Rightarrow invert_permut p f m]].
392 theorem invert_permut_f: \forall f:nat \to nat. \forall n,m:nat.
393 m \le n \to injn f n\to invert_permut n f (f m) = m.
398 rewrite > (eqb_n_n (f O)).simplify.reflexivity.
400 rewrite > (eqb_n_n (f (S m1))).simplify.reflexivity.
402 rewrite > (not_eq_to_eqb_false (f m) (f (S n1))).
404 apply injn_Sn_n. assumption.
405 unfold Not.intro.absurd (m = S n1).
406 apply H3.apply le_S.assumption.apply le_n.assumption.
408 apply (not_le_Sn_n n1).rewrite < H5.assumption.
411 theorem injective_invert_permut: \forall f:nat \to nat. \forall n:nat.
412 permut f n \to injn (invert_permut n f) n.
417 generalize in match (Hcut i H1).intro.
418 generalize in match (Hcut j H2).intro.
424 rewrite < (invert_permut_f f n a).
425 rewrite < (invert_permut_f f n a1).
428 assumption.assumption.
429 unfold permut in H.elim H. assumption.
431 unfold permut in H.elim H. assumption.
432 apply permut_to_bijn.assumption.
435 theorem permut_invert_permut: \forall f:nat \to nat. \forall n:nat.
436 permut f n \to permut (invert_permut n f) n.
437 intros.unfold permut.split.
438 intros.simplify.elim n.
439 simplify.elim (eqb i (f O)).simplify.apply le_n.simplify.apply le_n.
440 simplify.elim (eqb i (f (S n1))).simplify.apply le_n.
441 simplify.apply le_S. assumption.
442 apply injective_invert_permut.assumption.
445 theorem f_invert_permut: \forall f:nat \to nat. \forall n,m:nat.
446 m \le n \to permut f n\to f (invert_permut n f m) = m.
448 apply (injective_invert_permut f n H1).
449 unfold permut in H1.elim H1.
451 cut (permut (invert_permut n f) n).unfold permut in Hcut.
452 elim Hcut.apply H4.assumption.
453 apply permut_invert_permut.assumption.assumption.
454 apply invert_permut_f.
455 cut (permut (invert_permut n f) n).unfold permut in Hcut.
456 elim Hcut.apply H2.assumption.
457 apply permut_invert_permut.assumption.
458 unfold permut in H1.elim H1.assumption.
461 theorem permut_n_to_eq_n: \forall h:nat \to nat.\forall n:nat.
462 permut h n \to (\forall m:nat. m < n \to h m = m) \to h n = n.
463 intros.unfold permut in H.elim H.
464 cut (invert_permut n h n < n \lor invert_permut n h n = n).
466 rewrite < (f_invert_permut h n n) in \vdash (? ? ? %).
468 rewrite < (f_invert_permut h n n) in \vdash (? ? % ?).
469 apply H1.assumption.apply le_n.assumption.apply le_n.assumption.
470 rewrite < H4 in \vdash (? ? % ?).
471 apply (f_invert_permut h).apply le_n.assumption.
472 apply le_to_or_lt_eq.
473 cut (permut (invert_permut n h) n).
474 unfold permut in Hcut.elim Hcut.
476 apply permut_invert_permut.assumption.
479 theorem permut_n_to_le: \forall h:nat \to nat.\forall k,n:nat.
480 k \le n \to permut h n \to (\forall m:nat. m < k \to h m = m) \to
481 \forall j. k \le j \to j \le n \to k \le h j.
482 intros.unfold permut in H1.elim H1.
483 cut (h j < k \lor \not(h j < k)).
484 elim Hcut.absurd (k \le j).assumption.
486 cut (h j = j).rewrite < Hcut1.assumption.
487 apply H6.apply H5.assumption.assumption.
489 apply not_lt_to_le.assumption.
490 apply (decidable_lt (h j) k).
495 let rec map_iter_i k (g:nat \to nat) f (i:nat) \def
498 | (S k) \Rightarrow f (g (S (k+i))) (map_iter_i k g f i)].
500 theorem eq_map_iter_i: \forall g1,g2:nat \to nat.
501 \forall f:nat \to nat \to nat. \forall n,i:nat.
502 (\forall m:nat. i\le m \to m \le n+i \to g1 m = g2 m) \to
503 map_iter_i n g1 f i = map_iter_i n g2 f i.
504 intros 5.elim n.simplify.apply H.apply le_n.
505 apply le_n.simplify.apply eq_f2.apply H1.simplify.
506 apply le_S.apply le_plus_n.simplify.apply le_n.
507 apply H.intros.apply H1.assumption.simplify.apply le_S.assumption.
510 (* map_iter examples *)
512 theorem eq_map_iter_i_sigma: \forall g:nat \to nat. \forall n,m:nat.
513 map_iter_i n g plus m = sigma n g m.
514 intros.elim n.simplify.reflexivity.
516 apply eq_f.assumption.
519 theorem eq_map_iter_i_pi: \forall g:nat \to nat. \forall n,m:nat.
520 map_iter_i n g times m = pi n g m.
521 intros.elim n.simplify.reflexivity.
523 apply eq_f.assumption.
526 theorem eq_map_iter_i_fact: \forall n:nat.
527 map_iter_i n (\lambda m.m) times (S O) = (S n)!.
529 simplify.reflexivity.
531 (((S n1)+(S O))*(map_iter_i n1 (\lambda m.m) times (S O)) = (S(S n1))*(S n1)!).
532 rewrite < plus_n_Sm.rewrite < plus_n_O.
533 apply eq_f.assumption.
536 theorem eq_map_iter_i_transpose_l : \forall f:nat\to nat \to nat.associative nat f \to
537 symmetric2 nat nat f \to \forall g:nat \to nat. \forall n,k:nat.
538 map_iter_i (S k) g f n = map_iter_i (S k) (\lambda m. g (transpose (k+n) (S k+n) m)) f n.
539 intros.apply (nat_case1 k).
540 intros.simplify.fold simplify (transpose n (S n) (S n)).
541 rewrite > transpose_i_j_i.
542 rewrite > transpose_i_j_j.
546 (f (g (S (S (m+n)))) (f (g (S (m+n))) (map_iter_i m g f n)) =
547 f (g (transpose (S m + n) (S (S m) + n) (S (S m)+n)))
548 (f (g (transpose (S m + n) (S (S m) + n) (S m+n)))
549 (map_iter_i m (\lambda m1. g (transpose (S m+n) (S (S m)+n) m1)) f n))).
550 rewrite > transpose_i_j_i.
551 rewrite > transpose_i_j_j.
554 rewrite < (H1 (g (S m + n))).
557 intros.simplify.unfold transpose.
558 rewrite > (not_eq_to_eqb_false m1 (S m+n)).
559 rewrite > (not_eq_to_eqb_false m1 (S (S m)+n)).
562 apply (lt_to_not_eq m1 (S ((S m)+n))).
563 unfold lt.apply le_S_S.change with (m1 \leq S (m+n)).apply le_S.assumption.
564 apply (lt_to_not_eq m1 (S m+n)).
565 simplify.unfold lt.apply le_S_S.assumption.
568 theorem eq_map_iter_i_transpose_i_Si : \forall f:nat\to nat \to nat.associative nat f \to
569 symmetric2 nat nat f \to \forall g:nat \to nat. \forall n,k,i:nat. n \le i \to i \le k+n \to
570 map_iter_i (S k) g f n = map_iter_i (S k) (\lambda m. g (transpose i (S i) m)) f n.
571 intros 6.elim k.cut (i=n).
573 apply (eq_map_iter_i_transpose_l f H H1 g n O).
574 apply antisymmetric_le.assumption.assumption.
575 cut (i < S n1 + n \lor i = S n1 + n).
578 (f (g (S (S n1)+n)) (map_iter_i (S n1) g f n) =
579 f (g (transpose i (S i) (S (S n1)+n))) (map_iter_i (S n1) (\lambda m. g (transpose i (S i) m)) f n)).
580 apply eq_f2.unfold transpose.
581 rewrite > (not_eq_to_eqb_false (S (S n1)+n) i).
582 rewrite > (not_eq_to_eqb_false (S (S n1)+n) (S i)).
583 simplify.reflexivity.
584 simplify.unfold Not.intro.
585 apply (lt_to_not_eq i (S n1+n)).assumption.
586 apply inj_S.apply sym_eq. assumption.
587 simplify.unfold Not.intro.
588 apply (lt_to_not_eq i (S (S n1+n))).simplify.unfold lt.
589 apply le_S_S.assumption.
590 apply sym_eq. assumption.
591 apply H2.assumption.apply le_S_S_to_le.
594 apply (eq_map_iter_i_transpose_l f H H1 g n (S n1)).
595 apply le_to_or_lt_eq.assumption.
598 theorem eq_map_iter_i_transpose:
599 \forall f:nat\to nat \to nat.
600 associative nat f \to symmetric2 nat nat f \to \forall n,k,o:nat.
601 \forall g:nat \to nat. \forall i:nat. n \le i \to S (o + i) \le S k+n \to
602 map_iter_i (S k) g f n = map_iter_i (S k) (\lambda m. g (transpose i (S(o + i)) m)) f n.
606 apply (nat_case m ?).
608 apply (eq_map_iter_i_transpose_i_Si ? H H1).
609 exact H3.apply le_S_S_to_le.assumption.
611 apply (trans_eq ? ? (map_iter_i (S k) (\lambda m. g (transpose i (S(m1 + i)) m)) f n)).
613 unfold lt. apply le_n.assumption.
614 apply (trans_le ? (S(S (m1+i)))).
615 apply le_S.apply le_n.assumption.
616 apply (trans_eq ? ? (map_iter_i (S k) (\lambda m. g
617 (transpose i (S(m1 + i)) (transpose (S(m1 + i)) (S(S(m1 + i))) m))) f n)).
618 apply (H2 O ? ? (S(m1+i))).
619 unfold lt.apply le_S_S.apply le_O_n.id.
620 apply (trans_le ? i).assumption.
621 change with (i \le (S m1)+i).apply le_plus_n.
623 apply (trans_eq ? ? (map_iter_i (S k) (\lambda m. g
624 (transpose i (S(m1 + i))
625 (transpose (S(m1 + i)) (S(S(m1 + i)))
626 (transpose i (S(m1 + i)) m)))) f n)).
628 unfold lt. apply le_n.assumption.
629 apply (trans_le ? (S(S (m1+i)))).
630 apply le_S.apply le_n.assumption.
633 apply sym_eq. apply eq_transpose.
635 apply (not_le_Sn_n i).
636 rewrite < H7 in \vdash (? ? %).
637 apply le_S_S.apply le_S.
640 apply (not_le_Sn_n i).
641 rewrite > H7 in \vdash (? ? %).
645 apply (not_eq_n_Sn (S m1+i)).
646 apply sym_eq.assumption.
649 theorem eq_map_iter_i_transpose1: \forall f:nat\to nat \to nat.associative nat f \to
650 symmetric2 nat nat f \to \forall n,k,i,j:nat.
651 \forall g:nat \to nat. n \le i \to i < j \to j \le S k+n \to
652 map_iter_i (S k) g f n = map_iter_i (S k) (\lambda m. g (transpose i j m)) f n.
655 cut ((S i) < j \lor (S i) = j).
657 cut (j = S ((j - (S i)) + i)).
659 apply (eq_map_iter_i_transpose f H H1 n k (j - (S i)) g i).
661 rewrite < Hcut1.assumption.
663 apply plus_minus_m_m.apply lt_to_le.assumption.
665 apply (eq_map_iter_i_transpose_i_Si f H H1 g).
667 assumption.apply le_S_S_to_le.
668 apply (trans_le ? j).assumption.assumption.
669 apply le_to_or_lt_eq.assumption.
672 theorem eq_map_iter_i_transpose2: \forall f:nat\to nat \to nat.associative nat f \to
673 symmetric2 nat nat f \to \forall n,k,i,j:nat.
674 \forall g:nat \to nat. n \le i \to i \le (S k+n) \to n \le j \to j \le (S k+n) \to
675 map_iter_i (S k) g f n = map_iter_i (S k) (\lambda m. g (transpose i j m)) f n.
677 apply (nat_compare_elim i j).
678 intro.apply (eq_map_iter_i_transpose1 f H H1 n k i j g H2 H6 H5).
680 apply eq_map_iter_i.intros.
681 rewrite > (transpose_i_i j).reflexivity.
683 apply (trans_eq ? ? (map_iter_i (S k) (\lambda m:nat.g (transpose j i m)) f n)).
684 apply (eq_map_iter_i_transpose1 f H H1 n k j i g H4 H6 H3).
686 intros.apply eq_f.apply transpose_i_j_j_i.
689 theorem permut_to_eq_map_iter_i:\forall f:nat\to nat \to nat.associative nat f \to
690 symmetric2 nat nat f \to \forall k,n:nat.\forall g,h:nat \to nat.
691 permut h (k+n) \to (\forall m:nat. m \lt n \to h m = m) \to
692 map_iter_i k g f n = map_iter_i k (\lambda m.g(h m)) f n.
694 [simplify.rewrite > (permut_n_to_eq_n h)
695 [reflexivity|assumption|assumption]
696 |apply (trans_eq ? ? (map_iter_i (S n) (\lambda m.g ((transpose (h (S n+n1)) (S n+n1)) m)) f n1))
697 [unfold permut in H3.
699 apply (eq_map_iter_i_transpose2 f H H1 n1 n ? ? g)
700 [apply (permut_n_to_le h n1 (S n+n1))
701 [apply le_plus_n|assumption|assumption|apply le_plus_n|apply le_n]
706 |apply (trans_eq ? ? (map_iter_i (S n) (\lambda m.
707 (g(transpose (h (S n+n1)) (S n+n1)
708 (transpose (h (S n+n1)) (S n+n1) (h m)))) )f n1))
709 [simplify.fold simplify (transpose (h (S n+n1)) (S n+n1) (S n+n1)).
712 rewrite > transpose_i_j_j.
713 rewrite > transpose_i_j_i.
714 rewrite > transpose_i_j_j.
716 |apply (H2 n1 (\lambda m.(g(transpose (h (S n+n1)) (S n+n1) m))))
717 [apply permut_S_to_permut_transpose.assumption
720 rewrite > (not_eq_to_eqb_false (h m) (h (S n+n1)))
721 [rewrite > (not_eq_to_eqb_false (h m) (S n+n1))
722 [simplify.apply H4.assumption
725 apply (trans_lt ? n1)
726 [assumption|simplify.unfold lt.apply le_S_S.apply le_plus_n]
730 |unfold permut in H3.elim H3.
731 simplify.unfold Not.intro.
732 apply (lt_to_not_eq m (S n+n1))
733 [apply (trans_lt ? n1)
734 [assumption|simplify.unfold lt.apply le_S_S.apply le_plus_n]
736 apply (H7 m (S n+n1))
737 [apply (trans_le ? n1)
738 [apply lt_to_le.assumption|apply le_plus_n]
746 |apply eq_map_iter_i.intros.
747 rewrite > transpose_transpose.reflexivity